2015
DOI: 10.1007/s00709-015-0854-x
|View full text |Cite
|
Sign up to set email alerts
|

Sulcia symbiont of the leafhopper Macrosteles laevis (Ribaut, 1927) (Insecta, Hemiptera, Cicadellidae: Deltocephalinae) harbors Arsenophonus bacteria

Abstract: The leafhopper Macrosteles laevis, like other plant sap-feeding hemipterans, lives in obligate symbiotic association with microorganisms. The symbionts are harbored in the cytoplasm of large cells termed bacteriocytes, which are integrated into huge organs termed bacteriomes. Morphological and molecular investigations have revealed that in the bacteriomes of M. laevis, two types of bacteriocytes are present which are as follows: bacteriocytes with bacterium Sulcia and bacteriocytes with Nasuia symbiont. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 54 publications
(98 reference statements)
4
87
0
Order By: Relevance
“…Previous studies of symbiotic systems in Deltocephalinae leafhoppers have shown that members of this subfamily are characterized by diverse types of symbionts (BUCHNER 1925, 1965, MÜLLER 1962, SACCHI et al 2008, WANGKEEREE et al 2011, NODA et al 2012, ISHII et al 2013, KOBIAŁKA et al 2015. As a rule, the Deltocephalinae leafhoppers harbour the bacterium Sulcia and the betaproteobacterium Nasuia (WANGKEEREE et al 2011, NODA et al 2012, ISHII et al 2013, KOBIAŁKA et al 2015, this study) which MÜLLER (1962) termed a-symbionts and t-symbionts, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies of symbiotic systems in Deltocephalinae leafhoppers have shown that members of this subfamily are characterized by diverse types of symbionts (BUCHNER 1925, 1965, MÜLLER 1962, SACCHI et al 2008, WANGKEEREE et al 2011, NODA et al 2012, ISHII et al 2013, KOBIAŁKA et al 2015. As a rule, the Deltocephalinae leafhoppers harbour the bacterium Sulcia and the betaproteobacterium Nasuia (WANGKEEREE et al 2011, NODA et al 2012, ISHII et al 2013, KOBIAŁKA et al 2015, this study) which MÜLLER (1962) termed a-symbionts and t-symbionts, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Recent analyses have shown that in some cicadomorphans (e.g. Aphrophora quadrinotata SAY, 1830, Macrosteles laevis (RIBAUT, 1927)) more than two obligate symbionts may occur (KOGA et al 2013, KOBIAŁKA et al 2015. According to KOGA et al (2013), the presence of three symbionts (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the loss of critical translation-related genes in Tremblaya, the symbiosis would persist with a bacteria within a bacterium structure because no other structure is possible. We note that Sodalis-and Arsenophonus-allied symbionts were recently suggested to sometimes reside within Sulcia cells in the leafhoppers Cicadella viridis and Macrosteles laevis (66,67). Although these studies were based only on EM imaging and not confirmed by specific probes (e.g., with FISH), it is possible that symbioses formed by bacteria taking up residence inside of degenerate symbionts with host-derived cell envelopes are not uncommon.…”
Section: Diversity Of Intra-tremblaya Symbiont Genomes Suggests Multiplementioning
confidence: 92%